Descentralizaç\~ao federativa e desafios de implementaç\~ao do Programa Nacional de Alimentaç\~ao Escolar: Uma análise Pós-Lei No 11.947/2009 - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This text aims to analytically reflect on the decentralized execution process of the National School Feeding Program (PNAE), especially after an innovation that occurred through Law No. 11.947/2009, with the requirement that all federative entities commit a minimum of 30% of financial transfers received from the federal government for the purchase of food products directly from family farmers. We sought to investigate the proposed instruments to encourage adherence and coordination rules to be followed between subnational units in order to achieve the purpose set out in the program's new regulatory framework. According to the analyzes carried out, despite being a change that made the process of decentralized execution of the PNAE more complex, there was an effort on the part of local managers to move in the direction provided for by Law No. 11.947/2009, even if marked by large differences in execution in the national territory with regard to the average acquisition of family farming.
Keywords: H83; J23; 330; school feeding; family farming; public administration; federalism; local development